In Search of Income Convergence and Ideal Distribution – the Case of European Union Regions - Bal‑Domańska, Beata (Comparative Economic Research. Central and Eastern Europe, 2024)
In the field of economics and regional research, income convergence between countries and regions has been analysed since the 1980s. At the beginning of the 21st century, a number of articles addressing income convergence of European Union (EU) countries were published, which was among many topics related to the accession of 12 countries to the EU between 2004 and 2007. The inspiration for this study was the variety of conclusions about convergence in various groups of EU regions. The purpose of this article is to discuss the existing knowledge on the economic convergence of the EU regions and to expand it with the research results covering the period 2000–2021. The results confirm the convergence of incomes within EU regions, which translates into a change in the geographical distribution of income in the EU, slowly blurring the boundaries between the regions of the 2004/2007 enlargement countries and the countries located in the west and south of the EU. At the same time, no convergence within most of the biggest EU countries nor regions with well-developed knowledge-intensive sectors, were recorded.